Experiences of The Change Process During Emotion Focused Group Therapy - Sharbanee, Jason; Rauchelle, Kirra; Nelson, Marina; Gringart, Eyal (Taylor & Francis, 2024)
Emotion Focused Group Therapy has demonstrated preliminary efficacy for multiple syndromes. The groups involve individual chair-work in the context of the group, followed by interpersonal processing of the aroused emotions. So far there has been limited investigation of the mechanisms of change, including participants’ experiences of the change process. This study aimed to qualitatively examine participants’ experiences of the change process during Emotion Focused Group Therapy. Sixteen participants were interviewed about their experiences of the change process during the therapy group. The interview was structured to move from overarching reflections on the process of change, to specific experiences of their own chair-work and watching others’ chair-work. During the interview, participants were shown salient video segments of the group to prime their recall of moments of high arousal that were deemed likely to contain emotional change processes. Thematic Analysis extracted five main themes: Value of Vulnerability; Connectedness; Vicarious Emotional Processing; Understanding My Critic; and Barriers to Emotional Processing. These findings suggest that there may be both common and unique change processes that occur during Emotion Focused Group Therapy, compared with the individual Emotion Focused Therapy.